Participation of the Republic of Belarus in the Eurasian Economic Union: constitutional law evaluation - Nazarova, Olga (Journal of the Belarusian State University. Law, 2019)
Participation of the Republic of Belarus in integration associations is a challenge for the Belarusian legal science, as it poses a wide range of new topical issues for researchers. The article explores the issues of the correlation of supranationality within the Eurasian Economic Union with the provisions of the Constitution of the Republic of Belarus. The author examines the meaning of the term «supra-nationalism», including the example of the European Union. The author made analysis of the provisions of the Treaty on the Eurasian Economic Union related to the competence of the Union and its institutional structure and their relationship with the Constitution of the Republic of Belarus.
Keywords: Eurasian Economic Union; integration; supranationality; international organisations; sovereignty; constitution